Notulae to the Italian alien vascular flora: 13 - Gabriele Galasso; Gianniantonio Domina; Claudia Angiolini; Dario Azzaro; Gianluigi Bacchetta; Enrico Banfi; Davide Barberis; Giulio Barone; Fabrizio Bartolucci; Alessio Bertolli; Rossano Bolpagni; Gianmaria Bonari; et al. (Italian Botanist, 2022)
In this contribution, new data concerning the distribution of vascular flora alien to Italy are presented. It includes new records, confirmations, exclusions, and status changes for Italy or for Italian administrative regions. Nomenclatural and distribution updates published elsewhere are provided as Suppl. material 1.